PENGARUH KOMPETENSI DAN INDEPENDENSI AUDITOR TERHADAP KUALITAS AUDIT (STUDI : PADA KANTOR AKUNTAN PUBLIK DAN BADAN PEMERIKSA KEUANGAN DI SULAWESI UTARA) - Mailuhu, Roland; Mogi, Grace B.; Kalangi, Lintje (Universitas Sam Ratulangi, 2014)
Public accounting profession is a function of attestation/legalization (atesstation function). When auditors certify the information they publish a report with conclusions regarding the conviction of a written assertion from management. To produce a good quality audit, the auditor should perform the work in accordance with the auditing standards defined, ie in accordance with Standards on Auditing in the Public Accountants Professional Standards (SPAP) or the Auditing Standards for the State Audit Agency (BPK). The quality of the resulting audit the auditor may also be influenced by several factors, among others, competence and independence of the auditor. Competencies help auditors carry out the work effectively and efficiently. The auditor also should be independent in carrying out the audit. Because good competence would not be worth it if the auditor does not have the degree of independence in gathering and evaluating evidence. This study aims to analyze the influence of empirical evidence and prove the competence and independence by the Public Accountant (KAP) and North Sulawesi Representative BPK to audit quality. As for answering the research hypotheses using multiple regression analysis. Based on the partial results of the study it can be concluded that the competence of positive but not significant effect on audit quality and independence of positive and significant impact on audit quality. Competence and independence simultaneously jointly positive effect on audit quality. So the higher the competence and independence of the auditor, the better the quality of audits conducted.